The Principles of Advocacy Organization and Its Activities - ALEYNIKOV, Boris; ALEYNIKOVА, Anastasia (Journal of Advanced Research in Law and Economics, 2017)
The article gives a scientific study of the principles of advocacy. Formulated the concept and classification of principles of advocacy. On the basis of the sphere of dissemination of the principles of advocacy classified into fundamental principles (independence, professional competence, confidentiality, avoiding conflict of interest), organizational principles (territoriality, dependence of the judicial system, specialization, corporate governance, availability) and principles (efficiency, multidisciplinary approach, differentiated remuneration).